Втеча підлітків із дому як психологічна проблема - Ларіонов, С. О.; Larionov, S. O.; ORCID: http://orcid.org/0000-0002-3027-8535; Петленко, О. В.; Petlenko, O. V.; ORCID: http://orcid.org/0000-0003-2005-9600; Макаренко, П. В.; Makarenko, P. V.; ORCID: http://orcid.org/0000-0002-9055-3287 (Право і безпека. – 2014. – № 3 (54). – С. 226-230, 2014)
Розглянуто теоретико-психологічні аспекти проблеми втеч підлітків із дому. Проаналізовано класифікації підліткових утеч (емансипаційні, імпульсивні, демонстративні, дромоманічні) і самих підлітків-утікачів (тимчасові та навмисні). Узагальнено соціально-психологічні причини та безпосередні психологічні чинники втеч підлітків із дому. Проведено аналіз утечі підлітків із дому на різних рівнях організації поведінки, таких як: фізіологічна реакція, форма психологічного захисту, поведінкова реакція, симптом психологічного синдрому втечі від реальності, симптом поведінкового розладу.

This article represents theoretical and psychological aspects of the adolescent runaways from home. It is shown that there is a rejuvenation of runaway’s contingent, and there is a alteration of the runaway’s reasons towards individually psychological. It is described that teenagers’ runaways are classified for various reasons: duration (temporary and long-term), volitional (impulsive and deliberate), motivational (demonstrative and associated with fear of punishment), etc. It was analyzed the classification of teenage runaway (emancipatory, impulsive, demonstrative, dromomania) and teenagers runaway themselves (temporary and intentional). The summary of the social and psychological reasons: loss of parents due to the death or divorce; exile from home by parents; sexual assault; alcohol and drug abuse by adolescents; runaway or exile from home as a result of mental development defects or intellectual disability; requirements’ redundancy or the lack of attention from significant persons; anxiety due to the fear of punishment etc. Direct psychological factors of the runaway could be: 1) stress state of the teenager; 2) teenager’s view of the world, life plans and scenarios; 3) psychiatric disorders of personality and behavior; 4) teenager’s environmental features including a system of relations in the family and reference group. It is shown that teenager’s runaway from home it is a conscious, purposeful, action, analyzing which it is advisable to use common regularities including distinguishing of psychological factors and conditions. As any behavioral action runaway is considered in the context of personality, situation and their relation, as one of the ways of defensive behavior. It is noted that on the different levels of the behavior runaway could be considered as a physiological response, a form of psychological defense, behavioral reaction, a symptom of psychological syndrome of escape from reality, a symptom of behavioral disorder (dromomania).

Рассмотрены теоретико-психологические аспекты проблемы побегов подростков из дома. Проанализированы классификации подростковых побегов (эмансипационные, импульсивные, демонстративные, дромоманические) и самих подростков-беглецов (временные и умышленные). Обобщены социально-психологические причины и непосредственные психологические условия побегов подростков из дома. Проведён анализ побегов подростков из дома на разных уровнях организации поведения, таких как: физиологическая реакция, форма психологической защиты, поведенческая реакция, симптом психологического синдрома бегства от реальности, симптом поведенческого расстройства.
Teenagers’ runaway from their homes as a psychological problem
Побег подростков из дома как психологическая проблема
Ларіонов, С. О. Втеча підлітків із дому як психологічна проблема / С. О. Ларіонов, О. В. Петленко, П. В. Макаренко // Право і безпека. – 2014. – № 3 (54). – С. 226-230.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; підлітки; подростки; teenager; бродяжництво; бродяжничество; vagrancy; втеча з дому; побег из дома; runaway from home; девіантна поведінка; девиантное поведение; deviant behavior